Letter : Help for the Spanish Workers - Marchbank, John
028-0170-001 TELEGRAMS : "BEWARE, NORWEST, LONDON." TELEPHONE: EUSTON 4771, 5 LINES. The National Union of Railwaymen. Unity House, Euston Road, London, N.W.1. J. MARCHBANK, GENERAL SECRETARY. C. W. BROWN, ASSISTANT GENERAL SECRETARY. Your Ref: HVT/FC/30. In Your Reply Refer To: F.M.A.2. 19th October 1936. Mr. H. V. Tewson, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, HELP FOR THE SPANISH WORKERS. I am in receipt of your letter of the 14th instant, for which I thank you. I note the arrangements arrived at, and trust that the difficulties which have existed up to the time of writing will be removed by the appointing of the Committee for the handling of the relief. I also desire to thank you for the enclosures sent for my personal information. Yours faithfully, John Marchbank. 292/946/28/170